2006
DOI: 10.1111/j.1468-2982.2006.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Headache: Predictors of Onset and Recovery

Abstract: The objective of this study was to determine predictors of onset of new headache episodes and recovery from headache over one year. A population-based cohort study was conducted, comprising a baseline postal survey to a random sample of adults aged>or=18 years, with follow-up survey after 1 year. Risk factor data at baseline were compared with headache status at follow-up in two groups: (i) those free of recent headache at baseline and (ii) those with a recent headache at baseline. In respondents free of recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 38 publications
4
59
0
Order By: Relevance
“…However, in another HUNT study (25), good agreement was found for the diagnosis of migraine and the status of being a headache sufferer despite the fact that the questionnaire was filled in 5-9 months prior to interview. Boardman et al (26) found that the prevalence of headache was quite stable over time, but that some headache characteristics changed. Thus, it is likely that most participants with headache would have continued to report headache at the time of the MRI, but could have been classified to other headache groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another HUNT study (25), good agreement was found for the diagnosis of migraine and the status of being a headache sufferer despite the fact that the questionnaire was filled in 5-9 months prior to interview. Boardman et al (26) found that the prevalence of headache was quite stable over time, but that some headache characteristics changed. Thus, it is likely that most participants with headache would have continued to report headache at the time of the MRI, but could have been classified to other headache groups.…”
Section: Discussionmentioning
confidence: 99%
“…19,32,44 Although the direction of causality is not entirely clear, and is most likely bidirectional, several lines of evidence point to sleep problems as the primary antecedent factor. This includes evidence that insomnia exacerbates existing pain and predicts new-onset pain 5,25,35,46 as well as studies demonstrating that sleep quality predicts pain severity the next day.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, as epidemiological studies indicate that there is a causal relationship between insomnia and several painful disorders (Boardman et al, 2006;Canivet et al, 2008;Gupta et al, 2007;Hoogendoorn et al, 2001;Kaila-Kangas et al, 2006;Lyngberg et al, 2005;Odegard et al, 2011;Siivola et al, 2004), it would be interesting to find out whether these two observations are related or not. Specifically, if lack of sleep in healthy individuals result in LEP-habituation abnormalities, it might indicate that sleep loss could be the explanatory mechanism for the observed decreased LEP-habituation in migraine and fibromyalgia.…”
Section: Introductionmentioning
confidence: 98%